Zooming in on accretion – II. Cold circumgalactic gas simulated with a super-Lagrangian refinement scheme. Issue 3 (17th December 2018) - Suresh, Joshua; Nelson, Dylan; Genel, Shy; Rubin, Kate H R; Hernquist, Lars
ABSTRACT: In this study we explore the complex multiphase gas of the circumgalactic medium (CGM) surrounding galaxies. We propose and implement a novel, super-Lagrangian 'CGM zoom' scheme in the moving-mesh code arepo, which focuses more resolution into the CGM and intentionally lowers resolution in the dense interstellar medium. We run two cosmological simulations of the same galaxy halo, once with a simple 'no feedback' model, and separately with a more comprehensive physical model including galactic-scale outflows as in the Illustris simulation. Our chosen halo has a total mass of ∼10 12 M⊙ at z ∼ 2, and we achieve a median gas mass (spatial) resolution of ≃2200 solar masses (≃95 pc) in the CGM, six-hundred (fourteen) times better than in the Illustris-1 simulation, a higher spatial resolution than any cosmological simulation at this mass scale to date. We explore the primary channel(s) of cold-phase CGM gas production in this regime. We find that winds substantially enhance the amount of cold gas in the halo, also evidenced in the covering fractions of H i and the equivalent widths of Mg ii out to large radii, in better agreement with observations than the case without galactic winds. Using a tracer particle analysis to follow the thermodynamic history of gas, we demonstrate how the majority of this cold, dense gas arises due to rapid cooling of the wind material interacting with the hot halo, and how large amounts of cold, ∼10 4 K gas can be produced and persist in galactic haloes with T vir ∼ 10 6 K. At the resolutions presently considered, the quantitative properties of the CGM we explore are not appreciably affected by the refinement scheme.